2011
DOI: 10.1016/j.mce.2011.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and reproductive disorders

Abstract: Ghrelin is an important factor involved in most of the metabolic and hormonal signals which adapt the reproductive functions in conditions of altered energy balance. Moreover, the coordinated role of leptin and ghrelin appears in fact to have a specific role in the regulation of puberty. Systemic action of ghrelin on the reproductive axis involves the control of the hypothalamic-pituitary-gondal axis. In addition, it has been shown that ghrelin may directly act at a gonadal level in both females and males. Ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 179 publications
0
24
0
4
Order By: Relevance
“…Ghrelin plays important roles for maintaining GH release and energy homeostasis in vertebrates (Kojima and Kangawa 2005). Ghrelin has several effects including regulation of reproductive functions, pregnancy and lactation (Repaci et al 2011). It was also proven to significantly inhibit, in a dose-dependent manner, stimulated testosterone secretion (García et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin plays important roles for maintaining GH release and energy homeostasis in vertebrates (Kojima and Kangawa 2005). Ghrelin has several effects including regulation of reproductive functions, pregnancy and lactation (Repaci et al 2011). It was also proven to significantly inhibit, in a dose-dependent manner, stimulated testosterone secretion (García et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its role in normal physiology, ghrelin has been associated with a number of disease processes, including obesity (Scerif et al 2011, Yi et al 2011, type 2 diabetes mellitus and hyperinsulinaemia (Ukkola 2011), gastrointestinal disease (Jeffery et al 2011), cardiovascular disease (Isgaard & Granata 2011), reproductive disorders (Repaci et al 2011), mental health (Steiger et al 2011) and cancer (Chopin et al 2011, Deboer 2011. Ghrelin may play a role in prostate cancer progression, and we have previously demonstrated that ghrelin mRNA and protein is expressed in prostate cancer cell lines and tissues and that ghrelin stimulates cell proliferation in prostate cancer cell lines (Jeffery et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Несмотря на то что в большинстве исследований было показано, что грелин уменьшает секрецию гонадотропин-рили-зинг и лютеинизирующего гормонов, есть исследова-ния, которые продемонстрировали стимулирующий эффект грелина на продукцию фолликулостимули-рующего гормона и лютеинизирующего гормона [28]. Однако доминирует теория, согласно которой грелин уменьшает секрецию лютеинизирующего гормона кос-венно, посредством ингибирования гонадотропин-ри-лизинг-гормона и подавления экспрессии гена Kiss1, ответственного за синтез кисспептина, играющего важную роль в регуляции полового созревания [28,29]. Новые данные убедительно показывают, что грелин и его рецепторы (GHS-R1a и GHS-R1b) присутствуют в тканях яичников млекопитающих.…”
unclassified
“…Новые данные убедительно показывают, что грелин и его рецепторы (GHS-R1a и GHS-R1b) присутствуют в тканях яичников млекопитающих. У человека грелин был выявлен в интерстициальных клетках, ооцитах и клетках желтого тела [28]. В связи с этим считается, что грелин играет роль системного и паракринного регулятора развития и созревания фолликулов.…”
unclassified
See 1 more Smart Citation